Helsinki adventure: Inside the 'design nation' - Gislason, Kari (News Limited, 2014)
A travel article about Helsinki exploring the city's design culture. I’M often told that I’m from Finland. Even those who’ve known me for years confuse it with my birthplace, which is, in fact, Iceland. I’m not sure why the two countries are mixed up in this way, but it might be that Iceland and Finland are, in a sense, the “other” Scandinavian nations – on different sides of the Nordic world, but in the mind joined as its outer borders.